Upper Secondary School Students’ Learning at Work: The Effect on Agency in School - Maria Erss; Krista Loogma (Social Sciences)
In light of the fact that an increasing number of upper secondary school students in Estonia work in parallel with attending school or during school holidays, the purpose of the study was to ascertain whether work experience and the competencies acquired through work are, in combination with other school-related (teacher agency support), personal (resilience, achievement in Estonian language, mathematics and history) and socio-demographic (gender and mother tongue) factors, related to student agency in school. The second aim was to broaden the understanding of what students learn at work. The study used a mixed-methods approach involving a survey of upper secondary students (aged 16–19, N = 3179) in 30 schools followed by qualitative interviews with 18–19-year-old students who have gained work experience (N = 13). The analysis comprises a hierarchical linear regression analysis (N = 1947) and a thematic analysis of the interviews. The results indicate that work experience, perseverance, teacher agency support, male gender and Estonian mother tongue are positively related to agency while various skills learned at work had no relationship and student achievement in history was only relevant before work experience was added to the model. The interviews showed that students develop skills related to, e.g., self-regulation, self-awareness, career-awareness, social skills and self-confidence through work.